Early Alarm on the First Occurrence of the Southern Giant Hornet Vespa soror du Buysson, 1905 (Vespidae) in Europe - Omar Sánchez; Leopoldo Castro; Álvaro Fueyo; Yaisel J. Borrell; Andrés Arias (Ecology and Evolution)
ABSTRACT An eco‐monitoring program to assess the biodiversity of insects affected by yellow‐legged hornet (Vespa velutina) trapping in the north of the Iberian Peninsula (Spain) revealed the first occurrence of the southern giant hornet Vespa soror (Hymenoptera, Vespidae) on the European continent. We present a detailed characterization, combining morphological characteristics and molecular tools for genetic identification, as well as key information on its identification with respect to other hornets found on the Iberian Peninsula. We discuss the most plausible pathways and vectors of introduction, its potential invasiveness, and subsequent impacts on host localities. Our preliminary results raise concerns about the potential threat of V. soror to human health and ecosystem dynamics, as it is a highly predatory species on other insects and even small vertebrates. Finally, this study confirms once again the usefulness of studying insects trapped in such traps for rapid response and early detection of inland invasive species. We also propose a common Spanish name for the species, “avispón sóror”.